50. INITIAL RESULTS OF APPLYING ECMO - V V FOR TREATING PATIENTS WITH SEVERE ACUTE RESPIRATORY DISTRESS SYNDROME AT INTENSIVE CARE DEPARTMENT OF NATIONAL LUNG HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Review the initial results of applying ECMO - VV for treating patients with severe acute respiratory distress syndrome (ARDS) at Intensive Care Department of National Lung Hospital in 2023.Method: Case-series study design, performed on 13 patients with severe ARDS who were technique applied ECMO - VV at the Intensive Care Department of National Lung Hospital.Results: 13 ARDS patients were treated with ECMO - VV technique at Intensive Care Department of National Lung Hospital in 2023. The study describes a series of cases. The average age is 53.6 ± 13.5 years old, men account for 8/13. Before ECMO - VV intervention, the average SOFA score was 6.77 ± 1.83. The median duration of ECMO intervention is 5 days, the longest period is 30 days. The most common complications are thrombocytopenia (
Keywords: Severe Pneumonia, Acute respiratory distress syndrome (ARDS), ECMO – VV.